2014
DOI: 10.2147/copd.s72762
|View full text |Cite
|
Sign up to set email alerts
|

Ease-of-use preference for the ELLIPTA® dry powder inhaler over a commonly used single-dose capsule dry powder inhaler by inhalation device-naïve Japanese volunteers aged 40 years or older

Abstract: BackgroundIn patients receiving inhaled medication, dissatisfaction with and difficulty in using the inhaler can affect treatment adherence. The incidence of handling errors is typically higher in the elderly than in younger people. The aim of the study was to assess inhaler preference for and handling errors with the ELLIPTA® dry powder inhaler (DPI), (GSK), compared with the established BREEZHALER™, a single-dose capsule DPI (Novartis), in inhalation device-naïve Japanese volunteers aged ≥40 years.MethodsIn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 11 publications
2
36
0
2
Order By: Relevance
“…As far as the new device Ellipta ® was concerned, misuse in device handling was far less frequent (3%), but inhalation errors were similar (70%) compared to any other device. Likewise, Komase et al reported an 11% frequency of erroneous operations in device handling; however, their evaluation was limited to device handling and did not include inhalation-related actions [19].…”
Section: Discussionmentioning
confidence: 99%
“…As far as the new device Ellipta ® was concerned, misuse in device handling was far less frequent (3%), but inhalation errors were similar (70%) compared to any other device. Likewise, Komase et al reported an 11% frequency of erroneous operations in device handling; however, their evaluation was limited to device handling and did not include inhalation-related actions [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, as the majority (40/44) of the studies included in the NMA were blinded, it is unlikely that these differences in inhaler type would be reflected in the results. Currently, while several studies have identified patient preferences between different inhaler types [53][54][55], there is limited evidence to demonstrate any differences in efficacy outcomes [56,57]. Further research is therefore required to inform optimal device design, improve compliance, reduce handling errors and, ultimately, improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In TABLE 7, the author has reported some studies where LAMA/device systems are compared in terms of preference, usability, inhaler use, satisfaction with use and willingness to continue the inhaler use [49,75,135,[142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157]. Unfortunately, these outcomes were assessed in various ways, ranging from a simple question to non-validated and validated proprietary questionnaires.…”
Section: Devicementioning
confidence: 99%